2021
DOI: 10.1523/eneuro.0539-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Environmental Enrichment to Phenotypic Variation in Mice and Rats

Abstract: The reproducibility and translation of neuroscience research is assumed to be undermined by introducing environmental complexity and heterogeneity. Rearing laboratory animals with minimal (if any) environmental stimulation is thought to control for biological variability but may not adequately test the robustness of our animal models. Standard laboratory housing is associated with reduced demonstrations of species typical behaviors and changes in neurophysiology that may impact the translation of research resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Approximately 70% of enrichment studies from 1985 to 2004 focused on laboratory animals, especially rodents. Publications on this topic appeared in the literature with increasing frequency from 1999 onward, related to growing interest from neuroscientists [ 45 ], and this trend has continued to date [ 46 ]. A PubMed search for “environmental enrichment” and “rats” or “mice” identified 662 publications from 2020 alone.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of enrichment studies from 1985 to 2004 focused on laboratory animals, especially rodents. Publications on this topic appeared in the literature with increasing frequency from 1999 onward, related to growing interest from neuroscientists [ 45 ], and this trend has continued to date [ 46 ]. A PubMed search for “environmental enrichment” and “rats” or “mice” identified 662 publications from 2020 alone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with rats have also shown a major influence of housing conditions on the affective state and cognitive bias, thus also the emotional well-being of laboratory animals [ 21 ]. In the context of the reproducibility crisis, it is worth noting that concerns that enrichment in general increases the variation in experimental results have not been confirmed [ 10 , 20 , 22 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This seems contrary to the general beneficial effects of EE. One possible explanation is sex differences in the response to EE, which has not been well studied in previous EE research which has tended to focus on males (Kentner et al, 2019b;Kentner et al, 2021). Of the work that has explored sex-differences, some studies in rats found an overall greater effects of EE for males than for females, in terms of locomotor activity (Elliott and Grunberg, 2005), social exploration (Peña et al, 2006), and social memory.…”
Section: Discussionmentioning
confidence: 99%